2021
DOI: 10.3389/fped.2021.744705
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Real Life of Lumacaftor–Ivacaftor Treatment in Adolescents With Cystic Fibrosis

Abstract: Background: The combination of the CFTR corrector lumacaftor (LUM) and potentiator ivacaftor (IVA) has been labeled in France since 2015 for F508del homozygote cystic fibrosis (CF) patients over 12 years. In this real-life study, we aimed (i) to compare the changes in lung function, clinical (e.g., body mass index and pulmonary exacerbations) and radiological parameters, and in sweat chloride concentration before and after initiation of LUM/IVA treatment; (ii) to identify factors associated with response to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Of note, however the French participants had an increase in FEV1pp 10 , while the US study did not, mentioning that US participants had a higher starting FEV1 compared to the phase 3 clinical trial 9 . Exacerbations were not improved in either study, while the US found no differences in hospitalizations, or PA infection 9 and the French analysis found no changes in oral or IV antibiotic usage or CT scan evaluations 10 . Improvement in FEV1pp was noted to have an inverse correlation with age at LUM/IVA initiation 10 .…”
Section: Lumacaftor/ivacaftormentioning
confidence: 77%
See 2 more Smart Citations
“…Of note, however the French participants had an increase in FEV1pp 10 , while the US study did not, mentioning that US participants had a higher starting FEV1 compared to the phase 3 clinical trial 9 . Exacerbations were not improved in either study, while the US found no differences in hospitalizations, or PA infection 9 and the French analysis found no changes in oral or IV antibiotic usage or CT scan evaluations 10 . Improvement in FEV1pp was noted to have an inverse correlation with age at LUM/IVA initiation 10 .…”
Section: Lumacaftor/ivacaftormentioning
confidence: 77%
“…Exacerbations were not improved in either study, while the US found no differences in hospitalizations, or PA infection 9 and the French analysis found no changes in oral or IV antibiotic usage or CT scan evaluations 10 . Improvement in FEV1pp was noted to have an inverse correlation with age at LUM/IVA initiation 10 . Neither study found a correlation between changes in SC and FEV1pp, BMI percentile or BMI 9,10 .…”
Section: Lumacaftor/ivacaftormentioning
confidence: 77%
See 1 more Smart Citation
“…Lumacaftor and ivacaftor serum levels were also not predictive of clinical response [ 33 ]. In 2021, Bui et al prospectively investigated the clinical, radiological, and metabolic response of LUM/IVA over 24 months in 40 adolescents with CF [ 35 ]. Lung function was found to increase by +5.8 percentage points 2 years after treatment initiation, while BMI Z -score and sweat chloride concentrations improved and were sustained over 24 months.…”
Section: Lumacaftor/ivacaftormentioning
confidence: 99%
“…Age at LUM/IVA initiation was lower in good responders and was associated with a greater ppFEV 1 change during the 2 years of treatment. There were no significant changes in exacerbation rates, antibiotic use, or CT scan scores [ 35 ].…”
Section: Lumacaftor/ivacaftormentioning
confidence: 99%